ENSILING CHARACTERISTICS AND NUTRITIVE VALUE OF CORN COBS AS AFFECTED BY ADDITION OF DIFFERENT LEVELS OF UREA AND SOLUBLE CARBOHYDRATES - & Mohammed, Saeed (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2017)
This study was carried out in vitro to investigate the effect of addition of different levels of dates honey (DH) as soluble carbohydrates (WSC) and urea on fermentation quality and nutritive value of corn cobs silages (CCS). CC was ensiled with 4 levels of DH, 4, 6, 8 or 10% and 3 levels of urea 0, 1.5 or 3%. CCS samples were packed in double layer nylon bags and kept anaerobically for 60 days. Results revealed that color of CCS samples were ranged between yellow and brown. Smell of diluted vinegar was detected in samples made with addition of DH only, whereas, those made with addition of low and high levels of urea were characterized with smell of diluted and concentrated ammonia respectively. Increasing DH level from 4 to 10% significantly (P˂0.05) decrease in neutral detergent fiber (NDF) and hemicellulose by 2.42 and 2.69% respectively, with significant (P˂0.01) increase in crude protein (CP) and ether extract (EE). Significant (P˂0.05) decrease in crude fiber (CF) and NDF with significant (P˂0.01) increase in CP and cellulose contents were noticed due to addition of urea. Results also showed a trend for pH to be reduced (P˂0.01) with increasing level of DH, but different responses to increased urea levels were shown, where values were 5.91, 6.17 and 6.95 at levels of 0, 1.5 and 3%. Increasing DH level (6 and 8%) significantly (P˂0.01) decrease silage ammonia nitrogen concentration as a percentage of total nitrogen (18.52 and 18.35) and increase concentration of total volatile fatty acids as a percentage of silage dry matter (DM) at higher levels (6.73 and 8.24%), however both concentrations were reversely responded to increase urea level. Lower DM loss and buffering capacity (BC) were recorded at the lower level of DH (41.86 and 43.60 meq NaOH/100 g DM), whereas the higher level was associated with better Fleig point (Fp). Regarding effect of levels of urea, lower (P˂0.01) DM loss and BC with higher (P˂0.01) Fp at the lower level were observed, the later was 63.16. Results of study also revealed that increasing level of DH decreased aerobic stability of CCS samples to 41 hours (h), but higher value of 43.5 was recorded at higher level of urea. Results also showed that in vitro DM digestibility of CCS was (P˂0.05) improved due to increasing levels of DH and urea, however, lower (P˂0.05) values were obtained with lower levels of these additives.